A Super-Microsurgery Training Model: The Mouse Caudal Artery Anastomosis Model - Wu, Xue-Qiang; Liu, Hui-Ren; Yu, Zhan-Yong; Wang, Yan; Sun, Ru-Tao; Wang, Li; Gao, Yuan (Frontiers in Surgery, 2022)
Objective: To establish a simple and practical model for super-microsurgery training using the middle caudal arteries of Kunming mice. Methods: A 凵-shaped incision was made approximately 1 cm from the root of the tail in the mouse, and the skin, together with the subcutaneous tissue, was turned up into a rectangular shape to the opposite side with exposure of the mouse middle caudal artery and the accompanying veins. The artery was freed for approximately 1 cm in length. The middle caudal artery was cut transversely at the site, and then the severed middle caudal artery was anastomosed end-to-end using 12-0 microsutures in the order of 6, 12, 3, and 9 o'clock with four stitches. Results: The mouse caudal artery had a constant anatomical location accompanied by a vein. The immediate postoperative patency after vascular anastomosis was 100% (15/15) in all mouse models, the postoperative patency was 100% (5/5), 80% (4/5), and 75% (3/4) at 24 hours, three days, and one week postoperatively, respectively. The outer diameter of the mouse middle caudal artery was 0.2 ~ 0.3 (0.22 ± 0.03) mm. The vascular anastomosis time was 6.5 ~ 15 (11.0 ± 2.5) minutes. Conclusion: The mouse middle caudal artery was superficially located and anatomically constant, making it easy to be located and exposed. The small size of the opening made it suitable for establishing a useful model for training in super-microsurgery vascular anastomoses.